Three Metachronous Osteosarcomas within 22 Years without Pulmonary Metastases: A Case Report and Review of the Literature - Ulrike Michaela Pirker-Frühauf; Jörg Friesenbichler; Katharina Rabitsch; Bernadette Liegl-Atzwanger; Thomas Bauernhofer; Reinhard Windhager; Andreas Leithner (Case Reports in Orthopedics)
Introduction. We present the extremely rare case of a patient with three metachronous osteosarcomas within 22 years without evident pulmonary manifestation of disease 30 years after first diagnosis. Case Presentation. In 1983, a high-grade osteosarcoma of the left distal femur was diagnosed in an 18-year-old Caucasian male. He received rotationplasty accompanied by pre- and postoperative chemotherapy. Ten years later, an osteoblastic osteosarcoma occurred in TH12. En bloc resection and pre- and postoperative chemotherapy followed. In 2005, the patient developed another high-grade osteosarcoma in his right distal femur. Treatment included a wide resection and reconstruction with a tumour endoprosthesis as well as (neo)adjuvant chemotherapy. After the third tumour occurrence, cytogenetic and molecular genetic examinations (p53, rb1) were performed, showing a normal genetic pattern. Screening for metastases never showed clinical evidence of extraskeletal tumour manifestation. Discussion. In patients presenting metachronous osteosarcoma, identification of their lesions clonality (second primary tumour or metastases) could lead to a better understanding of tumour development and help to filter patients who need extended long-term followup due to a higher risk of late occurring sarcoma recurrence.